Analisis Kandungan Asam Lemak Mudah Terbang dengan Penambahan Buah Sirih dalam Ransum Ruminansia (In-Vitro) - Nurtania Sudarmi; Widyaningrum (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2020)
The area of land in West Papua is the main capital in raising cattle. Further socialization is needed regarding the importance of paying attention to the basic nutritional needs of cattle. The use of local plants that are often used by the community, such as betel fruit, is a worthy study to be explored. However, people still do not know the other benefits contained in betel fruit. In order to obtain optimal results, the study was carried out with in vitro experiments. Data processing was performed using factorial completely randomized design with three replications. The treatment factors were differentiated based on the length of the betel fruit immersion process in ice water and the length of storage time. The analysis showed that cold storage of grass with betel fruit was successful in increasing the Volattile Fatty Acid component (P> 0.01). The habits of the people of West Papua in utilizing local plants, especially those with tannin, have been scientifically proven to be useful. Cold storage of betel fruit with the addition of grass as ration for cattle has a very significant effect on the levels of iC4 (as iso butyrate), nC4 (as n butyrate), iC5 (as iso valerate), and nC5 (as n valerate). In addition, the Papuan people's habit of adding local plants, especially betel fruit as additional feed has been scientifically proven to be useful. Keywords: Betel Fruit, Ruminants, Grass, In Vitro, VFA